A noção de problema nos Estudos da Tradução: um novo olhar teórico com exemplos do par linguístico espanhol/português - WAQUIL, Marina Leivas (2019)
This work derives from the proposal of translation from Spanish to Portuguese of one of the most fundamental works in the area of ”‹”‹Translation Studies, Traducción y Traductología: Introducción a la Traductología, of the Spanish translator, teacher and author Amparo Hurtado Albir, which takes up the main definitions, characteristics and notions of translation analysis from the most different theorists and their perspectives. According to Franco (2010), this is the 21st most cited work in translation studies, being the only publication published in the 21st century and, moreover, the only one in the Spanish language among the fifty most referenced ones. From this translation, and foreseeing the complexity of the translation process to be faced, we proposed to study theoretically and empirically one of the most central and at the same time less reflected in the Translation Studies: translation problems. For this, we revisit the notion of problem in general, resorting to mathematical-philosophical discussions, which have their origin in Plato and that have developed with the contribution of contemporary philosophers such as Henri Bergson and Gilles Deleuze. In addition, despite the lack of studies, we also carried out a bibliographical research in the translation literature, taking up three theorists who studied the notion, Mounin (1963), Lörsher (1991), Nord (1997) and the PACTE Group and Hurtado Albir (2011; 2013), analyzing their reflections and the categorizations proposed by these authors. From an exploratory study in which we translated the first chapter of Traducción y Traductología: Introducción a la Traductología, we identified and analyzed quantitatively and qualitatively the problems encountered, noting the expressive frequency of terminological problems. Based on this, we have proposed a new classification of translation problems, including that specific category. As a conclusion to highlight this research is the proposal of a conception about the notion of problem that understands it in a positive way, as a proposer of new knowledge and perspectives for the most diverse areas of knowledge.